Konsep Ihsân dalam Wacana Pendidikan Islam - Husni, Husni (Research and Development Institution, Darussalam Institute for Islamic Studies, 2019)
This article studies the concept of Ihsan (good deed) in the thought of ulama mufassirs (Muslim scholars interpretering the Qur’an). The result of the study being carried out by the writer is that the concept of ihsan being too narrowly interpreted, proves that it has wide interpretation in the thought of muffasirs. If so far among society the concept of ihsan has been narrowly interpreted on the good deed or doing good deed, so according to mufassirs, the concept means: (1) carrying out all obligations, (2) being patient to receive all the obligation and anything forbidden by God, (3) being obedient and always perfects his obedience in quality as well as in the way, (4) forgiving, (5) being sincere, (6) realizing the existence of God, (7) emphasizing the esoteric aspect rather than exoteric world, (8) knowledge, (9) being firm in the truthfulness, (10) havng understanding about the true teachings of God, (11) having good comprehension about the law appropriately applied among the Islamic society. The wide meaning of this concept because this concept is really expressed by the Koran in context. This article tries to attach the concept of Ihsan in several meanings about the education world